Headspace solid-phase microextraction - gas chromatography - mass spectrometry qualitative screening method for active compounds, adulterants and impurities in ecstasy tablets seized in Northern Santa Catarina State, Brazil - Nicolodi C.* (2024)
© 2024 Elsevier B.V.The present work describes the development of a headspace solid-phase microextraction (HS-SPME) followed by gas chromatography - mass spectrometry (GC-MS) method for the qualitative analysis of compounds in seized ecstasy tablets that can be easily implemented in regular laboratories. HS-SPME with a DVB/CAR/PDMS 50/30 µm fiber was used to extract the ecstasy pills’ components, including major and minor ones, in a single extraction/chromatographic run. For HS-SPME, the incubation time (0 min to 30 min), the extraction time (10 min to 40 min) and temperature (40 °C to 80 ºC), the buffer volume (3 mL to 8 mL), the buffer pH (6 to 9) and the NaCl concentration (0 mol/L to 6 mol/L) were evaluated using fractional factorial design. Different split ratios and detector voltages were also evaluated. The optimal compromise between sensitivity and peak resolution was found to be incubation and extraction at 65 ºC for 10 min and 25 min, respectively, 3 mL of pH 9 buffer containing 3 mol/L NaCl, using 40.0 mg of the powdered samples in a 15-mL amber glass vial, and an injection with a split ratio of 1:10 at 260 ºC for 10 min. Under optimal conditions, 44 samples from different seizures were analyzed. Seventy-five compounds were tentatively identified by the proposed method, including active substances, medicines, caffeine, safrole derivatives, synthesis intermediates and solvent residues. The number of tentatively identified compounds per sample varied from 8 to 24, with a mean of 15. Important findings in ecstasy samples, such as norcinamolaurin, α-methyl-1,3-benzodioxole-5-propanamide, α-methyl-3,4-methylenedioxyphenylpropionitrile, acetylsalicylic acid, piperonylonitrile, methyl isobutyl ketone, mesitylene, and 4-[3-(dimethylamino)propyl]− 2,6-dimethylphenol, identified with a frequency higher than 10%, are not found in the literature so far. The method precision, based on relative standard deviation of peak areas, ranged from 5% to 15%, depending on the compound. The method was shown to be simple, relatively fast, precise and a powerful tool for the identification of major and minor components in ecstasy tablets in a single analytical cycle, being useful for screening or quantitative purposes, if authentic standards are available.